Thinned Linear Optical Phased Array Design Through a Pareto-Optimal Synthesis Strategy - Xueqing Yang; Nicola Anselmi; Paolo Rocca (Sensors)
The design of a thinned linear optical phased array (OPA) comprising a collection of waveguide grating antennas (WGAs) is addressed in this work. Given a fully populated linear OPA with antennas located in a uniform grid, the problem of selecting which elements have to be removed or retained is formulated as an optimization one. To this end, the definition of the optimal thinning architecture is produced through a multi-objective optimization strategy with the goal of minimizing the number of required antenna elements while maintaining a low sidelobe level and narrow beam width. A set of representative results is presented, also considering realistic WGA modeling to assess the capabilities and the potentialities of the proposed approach.